Analyzing Trends and Exploring the Correlation Between Runoff and Precipitation in the Armand River Basin - Dariush Saeidi; Amir Gandomkar; Masoud NAsri (Sustainable Earth Trends)
This study examines temporal trends and discharge patterns over 35 years in the Armand River Basin using data collected from synoptic and hydrometric stations (1986-2020). Statistical analysis and graphical tests like the Mann-Kendall test, Pearson correlation, and Spearman correlation were employed. Results show a notable negative trend in average annual and winter precipitation at the Shahrekord station since 1994 and 1996, respectively, with other stations exhibiting decreasing rainfall trends across all seasons without a clear pattern. The analysis of runoff trends across hydrometric stations in the Armand Basin indicates a significant decrease in both annual and seasonal runoff, particularly notable in the summer season. These trends align with observed changes in precipitation across different seasons, confirming the decreasing runoff trend. Pearson's and Spearman's correlation coefficients show a statistically significant correlation (p < 0.05) between runoff and precipitation, with coefficients of 0.612 and 0.595, respectively, supporting this relationship. Regression variance analysis confirms the linear assumption of this relationship, illustrated by scatter diagrams depicting the intensity, direction, and type of relationship between the two variables in the Armand River basin. The linear graphs indicate a positive relationship between precipitation and runoff in the basin. This is evident from the upward slope of the points, moving from left to right. Additionally, the concentration of points around the regression line suggests a strong and intense relationship between runoff and precipitation in the studied basin.